Sensory evaluation : a practical handbook - Kemp, Sarah E.; Hollowood, Tracey; Hort, Joanne (Ames, Iowa : Wiley-Blackwell, 2009)
- Covers the "why" and "how to" of basic sensory evaluation techniques via step-by-step instructions - Unusually, covers a broad range of applications including food, beverages and personal care and household products - Spiral bound for ease of use in the testing environment.